Congolese Student Comprehension of CMMW: A Stumbling Stone to the Development of L2 Learners’ Acquisition (American Journal of Multidisciplinary Research and Innovation, 2024)
It is necessary to use Chinese Mandarin measure words (CMMW) when counting objects and actions with numbers, demonstratives, nouns and verbs. Compared to Mandarin, Lingala generally has no measure words. According to Lado’s (1957) contrastive analysis hypothesis (CAH), linguistic elements different from the learners’ native language create difficulties for them. This study uses an empirical research method to investigate L2 learners’ use of CMMW and the problems they encounter. In the empirical study, questionnaires and proficiency tests were used to collect information from the participants. A CMMW test was also designed to collect data on the application and use of different CMMW by Lingala native speakers. The results of the empirical study showed that CMMW are a difficult task for Lingala native speakers. The results of this study also showed that although Lingala native speakers have difficulties in using most of the CMMW categories, some measure words are easier to use than others. The Congolese students have stronger skills in weights and measures, collective nominal measure words and temporary nominal measure words. The main reason for the difficulties lies not only in the cross-linguistic differences between Chinese Mandarin and Lingala, but also in the complexity of some CMMW. After finding out the difficulties faced by the Congolese students learning CMMW, some preliminary suggestions for teaching CMMW in second language learning and application were proposed.